2022
DOI: 10.4102/sajhivmed.v23i1.1380
|View full text |Cite
|
Sign up to set email alerts
|

Understanding patients reinitiating antiretroviral therapy in two South African districts

Abstract: No abstract available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Even so, it appears likely that many patients opt to lie about prior exposure. Other research suggests that they have good reason for doing so, as clinics may refuse to reinitiate those who admit to prior default and/or may provide poorer service to them 28–30. Creating a clinic and community atmosphere that promotes honesty about prior exposure should also be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, it appears likely that many patients opt to lie about prior exposure. Other research suggests that they have good reason for doing so, as clinics may refuse to reinitiate those who admit to prior default and/or may provide poorer service to them 28–30. Creating a clinic and community atmosphere that promotes honesty about prior exposure should also be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, it appears likely that many patients opt to lie about prior exposure. Other research suggests that they have good reason for doing so, as clinics may refuse to re-initiate those who admit to prior default and/or may provide poorer service to them [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…One of their key findings suggests there is still progress to be made in normalizing return to care as a quarter of healthcare workers reported that patients are sent to the back of the queue and that transfer letters are required to receive care ( 19 ). Similarly, Rees et al ( 20 ) have called for being supportive of patients who are re-initiating ART after treatment interruptions, suggesting a need to remove judgment of patients who may be worried about re-initiation.…”
Section: Discussionmentioning
confidence: 99%